The Effect of Augmented Reality (AR) on Students' Motor Educability in Football Learning - Aulia Azzahra; Asep Sumpena; Sufyar Mudjianto (Journal of Physical Education Health and Sport, 2025)
Physical education in schools requires strategies that can improve not only motor skills (motor ability) but also motor educability, namely the ability of students to understand, imitate, and adapt to new movements efficiently. However, conventional learning in soccer games is often hampered by limited visualization of techniques and low student motivation. Augmented Reality (AR) technology offers a solution through interactive visualization and real-time feedback that can enrich the sensorimotor processing process. This study aims to analyze the effect of AR-based learning using Active Arcade on improving students’ motor educability compared to conventional learning. The study used a quasi-experimental design with a pretest–posttest control group model on 134 students of Junior High School 14 Bandung (n = 67 experimental; n = 67 control). Motor educability was measured using the Iowa Brace Test (21 items ; validity 0.92; reliability 0.96). The intervention lasted for five learning sessions. Data analysis used normality, homogeneity, paired sample t-test , and ANOVA to test the treatment effect by controlling for pretest scores ( α = 0.05). The results showed that both groups experienced significant improvement between pretest and posttest (p < 0.001). However, the AR group showed a higher and more stable average improvement than the control group. ANOVA test indicated a significant difference in posttest scores after controlling for the pretest (F(1,132) = 4.996, p = 0.027), indicating that AR-based learning resulted in better motor educability than conventional learning. These findings confirm that AR is effective in enhancing visual processing, motor attention, and student engagement, thus optimally enhancing movement learning abilities. Therefore, AR is recommended as an innovative approach in physical education, particularly for materials requiring precise and interactive understanding of movement techniques.